ANALISIS EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI USAHATANI PADI SAWAH DI LAHAN RAWA PASANG SURUT DESA SUNGAI KAKAP KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - SUTARMAN GAFUR, HERLINA, ERLINDA YURISINTHAE, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2019)
Herlina, Analysis Of Efficiency Use Of Production Factors Of Rice Farming In Tidal Swamp Land Sungai Kakap Village, Sungai Kakap Subdistrict, Kubu Raya Regency, under the guidance of Dr. Ir. Erlinda Yurisinthae, MP as the First Supervisor and Ir. Sutarman Gafur, M.Sc, Ph.D as the Second Supervisor. This research objectives to analyze the effect of production factors are land area, number of seeds, Urea fertilizer, NPK fertilizer, KCl fertilizer, herbicides, insecticides, fungicides and manpower to rice production and to analyze efficiency of production factors to the rice farming in tidal swamp land Sungai Kakap Village, Sungai Kakap Subdistrict, Kubu Raya Regency. The analytical method used in this research is survey method. The location was chosen intentionally in Sungai Kakap Village, Sungai Kakap Subdistrict, Kubu Raya Regency becouse this area is the center of producing rice in the Sungai Kakap Subdistrict, which consist of four orchards are Nirwana, Merpati, Merak, dan Garuda. The research sample of 35 farmers. This research used the data analysis with the Cobb Douglass Production Function and Efficiency.The result showed that factors are land area, NPK fertilizer, KCl fertilizer, herbicides and manpower partially significantly influence the production in the rice farming activities while the number of seeds, Urea fertilizer, insecticides and fungicides partially does not significantly affect the production in the rice farming. The use of production factors in the rice farming in Tidal Swamp Land Sungai Kakap Village, Sungai Kakap Subdistrict, Kubu Raya Regency in the form of land area, NPK fertilizer, KCl fertilizer, herbicides, insecticides, and fungicides are not efficient while number of seeds, Urea fertilizer and manpower are inefficient.Keywords: Rice, Farming, Efficiency, Cobb Douglass